(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Ensuring the stability of the constitution and law is also an important factor in state and society management. It is well known that justice cannot be found in a society that does not have a stable constitution and law. Ensuring the supremacy of the Constitution is visible in the direct application of its norms. This article analyzes the positive aspects of direct application of constitutional norms.